2015
DOI: 10.15690/vramn.v69.i3-4.999
|View full text |Cite
|
Sign up to set email alerts
|

The Airways Microbial Community Composition in Healthy Individuals and Bronchial Asthma Patients

Abstract: This review summarizes the results of studies on the composition of microbial communities in the airways of healthy individuals and patients with asthma. Modern molecular genetic technology of the microbial identification, which are based on a sequence determination of encoding proteins genes conserved regions. These regions form the 16s-subunit ribosomal RNA in microorganisms of different species. These genes are detected by sequencing markers characteristic of individual microorganisms and their phylogenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similar alterations in gut microbiota have also been observed in adults with asthma. Fedosenko et al ( 2014 ), Masik et al ( 2019 ), Zolnikova et al ( 2020 ), and Ozimek et al ( 2022 ), have observed changes in gut microbiota in adult patients with bronchial asthma, including an increase in the proportion of Proteobacteria and a decrease in bacteria that can produce butyrate and acetate. The changes in gut microbiota in asthma mainly include the decrease of gut microbial diversity, the decrease of the relative abundance of beneficial microorganisms (such as Faecalibacterium), and the reduction or even depletion of SCFAs-producing bacteria.…”
Section: Relationship Between Gut Microbiome and Susceptibility To As...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar alterations in gut microbiota have also been observed in adults with asthma. Fedosenko et al ( 2014 ), Masik et al ( 2019 ), Zolnikova et al ( 2020 ), and Ozimek et al ( 2022 ), have observed changes in gut microbiota in adult patients with bronchial asthma, including an increase in the proportion of Proteobacteria and a decrease in bacteria that can produce butyrate and acetate. The changes in gut microbiota in asthma mainly include the decrease of gut microbial diversity, the decrease of the relative abundance of beneficial microorganisms (such as Faecalibacterium), and the reduction or even depletion of SCFAs-producing bacteria.…”
Section: Relationship Between Gut Microbiome and Susceptibility To As...mentioning
confidence: 99%
“…Similar alterations in gut microbiota have also been observed in adults with asthma. Fedosenko et al (2014), Masik et al (2019), Zolnikova et al (2020), andOzimek et al (2022), have observed changes in gut microbiota in adult patients with bronchial asthma, including an increase in the proportion of Proteobacteria and a…”
mentioning
confidence: 99%
“…Patients with primarily Th2 immune response have a tendency to reduced concentration of immunoglobulins A and G in blood serum, of interferon γ and secretory immunoglobulins as well; to disturbed differentiation of immunocompetent cells; apparently, this results in persistent vulnerability to viruses. Moreover, recent studies of respiratory tract microbiota have demonstrated that bronchial tree of a virtually healthy person is characterized by low bacterial load (the most characteristic bacteria belong to genera Pseudomonas, Streptococcus, Prevotella, Fusobacteria and Veilonella; potentially pathogenic genera Haemophilus and Neisseria are observed far less often) [16]. In patients with bronchial asthma, lower respiratory tract microbiota undergoes qualitative transformation: amount of Proteobacteria increases, of Bacteroidetes -decreases (in comparison with healthy persons).…”
mentioning
confidence: 99%